HUBUNGAN ETIKA DENGAN PROFESI SERTA SIKAPNYA DAN PERMASALAHAN DALAM MASYARAKAT MODERN DI ERA DIGITALISASI - Muhammad Zakky Elyasin; Atsna Auliya Mahfudhoh; Muhamad Rizky Aditya (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Technological developments have a major impact on all levels of society, including the legal profession. The increasing availability of data, instant communication capabilities, and easier access to legal information are driving major changes in legal practice and requiring legal professionals to adapt to new technologies. While these changes create opportunities for increased efficiency, they also pose complex ethical challenges. This research is a type of library research, namely research whose main object is books, books, magazines, pamphlets, and other documentary materials. Therefore, in this study, in unraveling the problem of using texts related to morality and the Legal Profession in the Digital Era, ethical attitudes in modern law and law in social change, c. Ethical attitudes in modern law as a tool of social engineeringThe development of digital technology has brought significant changes in the field of medicine